A new fixed point theorem and periodic solutions of nonconservative weakly coupled systems. (March 2020) - Liu, Chunlian; Qian, Dingbian
Abstract: In this paper, we prove a new fixed point theorem for the coupling of twist conditions and Poincaré–Bohl type conditions, as its applications we prove the existence of periodic solutions for various nonconservative mixed type weakly coupled systems.